RADIOCARBON DATING OF MAKURI LÊ BOOM, A VERY OLD AFRICAN BAOBAB FROM NYAE NYAE, NAMIBIA - PATRUT, Roxana T.; PATRUT, Adrian; RAKOSY, Demetra; RAKOSY, Laszlo; LÖWY, Daniel A.; BODIS, Jenő; REDEN, von, Karl F. (Studia Universitatis Babeș-Bolyai Chemia, 2020)
The article reports the AMS (accelerator mass spectrometry) radiocarbon dating results of Makuri Lê boom, a very large African baobab from Nyae Nyae Conservancy, Namibia. The investigation of this superlative baobab shows that it consists of 12 independent stems of different dimensions, which belong to three generations. Makuri Lê boom has an open ring-shaped structure, a type of architecture which allows baobabs to reach very large sizes and old ages. The oldest sample has a radiocarbon date of 1602 ± 17 BP, which corresponds to a calibrated age of 1520 ± 35 calendar yr. By this value, Makuri Lê boom becomes one of the oldest dated baobabs and angiosperms with accurate dating results.